A Study of Physical and Mechanical Properties of Powder Injection Molded Copper-Tungsten Alloys - Shanmugam, Kashinath (2018)
The purpose of this paper is to study the mechanical and physical properties of the Copper-Tungsten composite that is developed through powder injection molding. In this paper attempt were made to develop feedstock of copper- tungsten alloy to be injection molded. The molded parts were solvent debinded, then followed by thermal debinding and sintering. The sintered part was characterize based on microstructure under optical microscope, Vickers hardness and calculated tensile strength. Base on the microscope structure of the sintered part were observed that the copper and tungsten is well dispersed. The hardness and tensile stress of the copper – tungsten alloy increases as the composition of tungsten increased.